DIGITAL LIBRARY OF AL-QUR`AN (DILIA) DARI KHAZANAH PESANTREN UNTUK DUNIA ISLAM - Achmad Zayadi (STAI ALHIKMAH Jakarta, 2016)
Abstract Nowadays Islamic boarding school has used Information and Communication Technologies (ICT) as learning method. Thus, honestly we also elaborate that ICT is still seldom used for needs of school library services. Although how students learn still much traditionally, their interaction with outside world causes they have many choices to determine how to learn. Their necessary on information quickly, easily, and accurately is not inevitable. Library as informative service media still seldom gives services related the students’ need. The library in boarding school is still seen styled with traditional concept and collection served to reader with analog model. Supposedly, the library needs to be reorganized with the service concept in a digital format. The writing on this scientific work is supposed to give concrete opinion in participating khazanah knowledge about reading resource that exists in Islamic boarding school. Because a book is the gate of science, if we don’t preserve by keeping book, so we will come into the hall of ignorance. This writing is little bit consulting to answer the problems about how to improve educational world in Islamic boarding school, one of them is to participate to keep preservation of reading materials and makes reader (read: students) interested and happy to read and become reading event as culture continuously. Keywords: Digital Libraries, Education of Islamic Boarding School (pesantren) Abstrak Dunia pesantren saat ini sudah banyak yang menggunakan ICT sebagai media belajar. Namun secara jujur juga kita ungkapkan bahwa ICT masih jarang digunakan untuk kebutuhan layanan perpustakaan pesantren. Walaupun cara belajar santri masih banyak yang tradisional, namun persinggungan mereka dengan dunia luar menyebabkan mereka punya banyak pilihan dalam menentukan cara belajar, kebutuhan mereka pada informasi yang cepat, mudah, dan akurat sudah tidak terelakkan lagi. Perpustakaan sebagai media layanan informasi masih jarang memberikan layanan yang sesuai dengan kebutuhan santri. Perpustakaan di pesantren masih terlihat ditata dengan konsep tradisional dan koleksipun dihidangkan ke pembaca dengan model analog. Seharusnya, perpustakaan perlu ditata ulang dengan konsep layanan dalam format digital. Tulisan dalam karya ilmiah ini dimaksudkan memberikan usulan konkrit di dalam ikut melestariskan khazanah keilmuan berupa sumber bacaan yang ada di Pesantren. Sebabbuku adalah gerbang ilmu, jika kita tidak menjaga kelestarian buku, maka kita sama saja masuk ke lorong kebodohan. Tulisan ini sedikit urun rembuk menjawab persoalan bagaimana memajukan dunia pendidikan di Pesantren, salah satunya adalah dengan turut serta menjaga kelestarian bahan bacaan dan menjadikan pembaca (baca: santri) tertarik dan senang untuk membaca dan menjadikan kegiatan membaca sebagai budaya yang kontinyu. Kata Kunci: Perpustakaan Digital, Pendidikan Pesantren